Is Ancestor veneration the most universal of all world religions? A critique of modernist cosmological bias - Reuter, Thomas (Wacana, Journal of the Humanities of Indonesia, 2014)
Research by anthropologists engaged with the Comparative Austronesia Project (Australian National University) has amassed an enormous data set for ethnological comparison between the religions of Austronesian-speaking societies, a language group to which nearly all Indonesian societies also belong. Comparative analysis reveals that ancestor veneration is a key-shared feature among "Austronesian" religious cosmologies; a feature that also resonates strongly with the ancestor-focused religions characteristic of East Asia. Characteristically, the religions of Austronesian-speaking societies focus on the core idea of a sacred time and place of ancestral origin and the continuous flow of life that is issuing forth from this source. Present-day individuals connect with the place and time of origin though ritual acts of retracing a historical path of migration to its source. What can this seemingly exotic notion of a flow of life reveal about the human condition writ large? Is it merely a curiosity of the ethnographic record of this region, a traditional religious insight forgotten even by many of the people whose traditional religion this is, but who have come under the influence of so-called world religions? Or is there something of great importance to be learnt from the Austronesian approach to life? Such questions have remained unasked until now, I argue, because a systematic cosmological bias within western thought has largely prevented us from taking Ancestor Religion and other forms of "traditional knowledge" seriously as an alternative truth claim. While I have discussed elsewhere the significance of Ancestor Religion in reference to my own research in highland Bali, I will attempt in this paper to remove this bias by its roots. I do so by contrasting two modes of thought: the "incremental dualism" of precedence characteristic of Austronesian cultures and their Ancestor Religions, and the "transcendental dualism" of mind and matter that has been a central theme within the cultural history of Western European thought. I argue for a deeper appreciation of Ancestor Religion as the oldest and most pervasive of all world religions. Keywords